2003
DOI: 10.1037/0096-1523.29.5.937
|View full text |Cite
|
Sign up to set email alerts
|

Top-down contingencies in peripheral cuing: The roles of color and location.

Abstract: According to contingent-processing accounts, peripheral cuing effects are due to the cues' inadvertent selection for processing by control settings set up for targets (e.g., C. L. Folk, R. W. Remington, & J. C. Johnston, 1992). Consequently, cues similar to targets should have stronger effects than do dissimilar cues. In the current study, this prediction is confirmed for cue-target combinations similar or dissimilar in the static features of color (Experiments 1-3) and location (Experiment 4), even when both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
93
4
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 58 publications
(132 reference statements)
11
93
4
5
Order By: Relevance
“…By contrast, the smallest compatibility effects were observed following the presentation of unimodal shape-incongruent distractors-that is, distractors that were very dissimilar from the target. The results of Experiment 2 are in line with the assumption that a decline in target-distractor similarity should decrease the potential of a distractor to attract attention automatically (see Ansorge & Heumann, 2003;Ansorge & Heumann, 2004;. Most important, however, is the observation that even in the shape-incongruent condition, larger compatibility effects were found after the presentation of a bimodal distractor than after the presentation of a unimodal distractor.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…By contrast, the smallest compatibility effects were observed following the presentation of unimodal shape-incongruent distractors-that is, distractors that were very dissimilar from the target. The results of Experiment 2 are in line with the assumption that a decline in target-distractor similarity should decrease the potential of a distractor to attract attention automatically (see Ansorge & Heumann, 2003;Ansorge & Heumann, 2004;. Most important, however, is the observation that even in the shape-incongruent condition, larger compatibility effects were found after the presentation of a bimodal distractor than after the presentation of a unimodal distractor.…”
Section: Discussionsupporting
confidence: 75%
“…If the subsequent target happened to have been presented from the same spatial location as the cue stimulus, processing was speeded up. These findings have now been replicated in numerous studies involving both spatial (Anderson & Folk, 2010;Ansorge & Heumann, 2003, 2004Eimer, Kiss, Press, & Sauter, 2009;Folk & Remington, 1998;Folk, Remington, & Wright, 1994) and nonspatial attentional blink (AB) tasks (Folk, Leber, & Egeth, 2008; see also Folk et al, 2002, for another AB task, but with spatial distractors). Taken together, such results provide robust support for the importance of top-down mechanisms in attentional capture.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…The average RTs were around or above 800 ms, longer than in any of the current conditions, and yet robust cuing effects were still found in all three experiments in that study. 4 One may argue that the attentional capture effect by onset could be due to color similarity (i.e., white) between the cue and the target (Ansorge & Heumann, 2003). The onset cue shares the same color as the onset target (white), but not the color target (red); therefore, it is expected to have a larger capture effect with an onset target than with a color target if color similarity plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has revealed an interaction between topdown settings and bottom-up signals on the control of attention (e.g., Anderson & Folk, 2010;Ansorge & Heumann, 2003;Folk & Remington, 1998Folk et al, 1992;Folk et al, 1994;Gibson & Kelsey, 1998; for reviews, see Burnham, 2007;Theeuwes, 2010). But according to the attentional disengagement account, all salient stimuli capture attention in a stimulus-driven manner.…”
Section: Response Time Distributionmentioning
confidence: 99%